PROMISE AND CHALLENGE OF E-LEARNING – LITERATURE REVIEW - Albidewi, Ibrahim; Tulb, Radi (European Scientific Journal, ESJ, 2014)
In this paper is presented the key findings from a literature review on the use of E-learning. The literature review presented here examines the promise and challenges associated with E-learning. Also, this paper reviews literature that deals with the definition of E-Learning 2.0 distinguishing it from traditional E-learning. The benefits of Elearning include a blending of formal and informal learning environments that open up new avenues of self service through experiential learning, while facilitating teamwork and community. While these benefits are fascinating, it is important to recognize that E-learning also poses challenges for educators and students alike. Finally, this paper is closed with conclusions and suggestions for future research on E-learning.